Consumption and performance by beef heifers provided dried distillers grains in a self-fed supplement containing either 10 or 16% salt while grazing Flint Hills native grass - Melton, N. T.; Oleen, Brandon E.; Vahl, Christopher I.; Montgomery, Sean P.; Schlegel, Ethan R.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Optimizing cattle performance and maintaining pasture health are important considerations when striving to maximize profitability and sustainability on a Flint Hills pasture yearling grazing operation. The two growing seasons prior to initiation of this study were droughty and stressful to pastures. This situation provided an opportunity to evaluate the value of dried distillers grains with solubles (DDGS) as a self-fed supplement to ensure that nutritional resources were adequate for a 78-day grazing period. Grazing density was increased from 200 to either 225 or 250 lb of beef while simultaneously providing salt-limited DDGS supplements containing 10 and 16% salt, respectively.
Keywords: Beef; Dried distillers grains; Grazing